Current insights and trends in atopic dermatitis and microbiota interactions: a systematic review and bibliometric analysis - Zhang, Zhongsong; Wang, Rong; Li, Mao; Lu, Mao (Frontiers in Microbiology, 2025)
BackgroundAtopic dermatitis (AD) is a prevalent chronic inflammatory skin condition influenced by immune dysfunction, genetics, and environmental factors, with emerging evidence highlighting the critical role of skin and gut microbiota in its pathogenesis. This article uniquely integrates a systematic review with bibliometric analysis to map the research landscape of AD and microbiota interactions, offering a comprehensive synthesis of trends and future directions.MethodsWe conducted a bibliometric analysis using the Web of Science Core Collection, retrieving 1,196 English-language articles and reviews published between 2009 and 2024, employing a detailed search strategy targeting AD and microbiota-related terms. Data were analyzed with tools like CiteSpace, VOSviewer, and Biblioshiny to assess publication trends, geographical contributions, institutional outputs, journal impacts, author networks, reference citations, and keyword evolution.ResultsResearch on AD and microbiota has surged since 2016, peaking at 168 publications in 2021, with the USA leading in output (360 papers) and citations (24,655). The University of Copenhagen and the Journal of Allergy and Clinical Immunology emerged as top contributors, while authors like Gallo, Richard L., and Kong, Heidi H. drove influential studies. Key findings underscore the skin and gut microbiomes as research hotspots, with Staphylococcus aureus and the gut-skin axis dominating discussions. Emerging trends from 2020 to 2024 focus on adult AD severity, prebiotics, and personalized interventions like fecal microbiota transplantation (FMT), supported by multi omics data.ConclusionThis study illuminates the dynamic growth and global collaboration in AD and microbiota research, emphasizing microbial dysbiosis and immune modulation as pivotal to AD management. These insights pave the way for precision medicine and dietary interventions, promising enhanced therapeutic strategies and improved patient outcomes through continued multidisciplinary efforts.